Does Learning Geography Increase Climate Change Awareness? A Comparison of School Subjects' Influence on Climate Change Awareness - Onuoha, Joseph; Eze, Emmanuel; Ezeaputa, Chidiebere Mary-Cynthia; Okpabi, Jacob Ugbada; Onyia, Jennifer Chioma (Journal of geography (Houston), 2021)
School subjects' curricula, including geography, are infused with contents to improve climate change literacy. This study sampled 420 public secondary school students in Enugu State, Nigeria. Mean differences and multinomial logistic regression results show geography students possess the highest climate change awareness level. Besides, students' gender, location, age and class are variables significantly influencing climate change awareness. Students who took geography had an increased probability of being moderately or highly aware of climate change. The scope of climate change contents infused in other school subjects ought to be expanded, with explicit specifications of methods and materials for delivery.